Moderate exercise training does not prevent the reduction in myocardial L-type Ca2+ channels protein expression at obese rats - Silva, Vitor L. da [UNESP]; Lima-Leopoldo, Ana P.; Ferron, Artur J. T. [UNESP]; Cordeiro, Joctan P.; Freire, Paula P. [UNESP]; Campos, Dijon H. S. de [UNESP]; Padovani, Carlos R. [UNESP]; Sugizaki, Mario M.; Cicogna, Antonio C. [UNESP]; Leopoldo, Andre S. (Wiley-Blackwell, 2017)
Authors have showed that obesity implicates cardiac dysfunction associated with myocardial L-type calcium channels (LTCCs) activity impairments, as well as moderate exercise training (MET) seems to be an important therapeutic tool. We tested the hypothesis that MET promotes improvements on LTCCS activity and protein expression at obesity induced by unsaturated high-fat diets, which could represent a protective effects against development of cardiovascular damage. Male Wistar rats were randomized in control (C, n = 40), which received a standard diet and obese (Ob; n = 40), which received high-fat diet. After 20 weeks, the animals were assigned at four groups: control (C; n = 12); control submitted to exercise training (ET; n = 14); obese (Ob; n = 10); and obese submitted to exercise training (ObET; n = 11). ET (5 days/week during 12 weeks) began in the 21th week and consisted of treadmill running that was progressively increased to reach 60 min. Final body weight (FBW), body fat (BF), adiposity index (AI), comorbidities, and hormones were evaluated. Cardiac remodeling was assessed by morphological and isolated papillary muscles function. LTCCs activity was determined using specific blocker, while protein expression of LTCCs was evaluated by Western blot. Unsaturated high-fat diet promoted obesity during all experimental protocol. MET controlled obesity process by decreasing of FBW, BF, and AI. Obesity implicated to LTCCs protein expression reduction and MET was not effective to prevent this condition. ET was efficient to promote several improvements to body composition and metabolic parameters; however, it was not able to prevent or reverse the downregulation of LTCCs protein expression at obese rats.
Keywords: Cardiac physiology; exercise training; myocardial L-type Ca2+ channels; obesity